2014
DOI: 10.1111/sbr.12053
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for obstructive sleep apnea in non-obese Korean patients: Significance of body weight

Abstract: The aim of this study is to evaluate if there is an association between body weight and obstructive sleep apnea even in patients who are not obese. From our hospital database, we identified 139 patients who underwent an overnight polysomnography. The inclusion criteria were patients (i) who visited our hospital with a chief complaint of snoring or apnea that was witnessed by a sleep partner, and (ii) with a body mass index <25 kg/m 2 . We compared the clinical variables, polysomnographic variables, and Epworth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
(80 reference statements)
1
6
0
Order By: Relevance
“…This is consistent with Park et al's results. 4) This study supports that nonobese patients with OSA can also benefit from weight loss, although this study did not demonstrate any direct evidence about a beneficial effect of weight loss on OSA in them.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…This is consistent with Park et al's results. 4) This study supports that nonobese patients with OSA can also benefit from weight loss, although this study did not demonstrate any direct evidence about a beneficial effect of weight loss on OSA in them.…”
Section: Discussionsupporting
confidence: 43%
“…Previous studies reported that neck circumference was one of the factors associated with the severity of OSA, even in nonobese. 4,5) Considering that neck circumference means the quantity of adipose tissue distribution around upper airway, our finding suggests that other pathogenic model is needed for nonobese patients with OSA, rather than earlier model (airway obstruction, especially at the level of oro and hypopharynx).…”
Section: Kjfpmentioning
confidence: 84%
See 1 more Smart Citation
“…Similarly, obesity has been known as a main risk factor for obstructive sleep apnea in humans, where the deposition of fat around the airways is associated with apnea predisposition 3,21 . Furthermore, there was a significant association between body weight and obstructive sleep apnea in non‐obese patients, and the apnea‐hypopnea index was positively correlated with body weight and neck circumference 22 . However, another study reported that pharyngeal collapsibility during sleep and preferential fat deposition around the upper airways were independent of body mass index (calculated as weight divided by height in meters squared) 23,24 .…”
Section: Discussionmentioning
confidence: 97%
“…3,21 Furthermore, there was a significant association between body weight and obstructive sleep apnea in non-obese patients, and the apnea-hypopnea index was positively correlated with body weight and neck circumference. 22 However, another study reported that pharyngeal collapsibility during sleep and preferential fat deposition around the upper airways were independent of body mass index (calculated as weight divided by height in meters squared). 23,24 This may reflect different aspects between body mass index and BCS, which relies on visual and palpable characteristics to estimate the degree of obesity.…”
Section: Discussionmentioning
confidence: 99%